2020
DOI: 10.3390/pr8010077
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity for Monitoring the Expansion of the Support Material in an Anaerobic Biofilm Reactor

Abstract: This article describes the use of the electrical conductivity for measuring bed expansion in a continuous anaerobic biofilm reactor in order to prevent the exit of support material from the reactor with the consequent loss of biomass. The substrate used for the tests is obtained from a two-stage anaerobic digestion (AD) process at the pilot scale that treats the liquid fraction of fruit and vegetable waste (FVW). Tests were performed with the raw substrate before anaerobic treatment (S1), the effluent from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
(59 reference statements)
4
4
0
Order By: Relevance
“…The study conducted by Marín-Peña et al showed the effect of conductivity on biogas generation concluded that conductivity above 14 mS/cm is ideal for the reactors. In the present study, conductivity gradually increased to an average of 15 to 30 µS/cm after 16 th day and was remained constant for the rest of the process [24].…”
Section: Pilot-scale Anaerobic Co-digestion Of Ofmsw and Sssupporting
confidence: 60%
See 2 more Smart Citations
“…The study conducted by Marín-Peña et al showed the effect of conductivity on biogas generation concluded that conductivity above 14 mS/cm is ideal for the reactors. In the present study, conductivity gradually increased to an average of 15 to 30 µS/cm after 16 th day and was remained constant for the rest of the process [24].…”
Section: Pilot-scale Anaerobic Co-digestion Of Ofmsw and Sssupporting
confidence: 60%
“…The results thus obtained reflect the proposed aim of the study. Studies carried out by Klein et al, and Marín-Peña et al showed that the conductivity of more than 30 mS/cm has shown an adverse effect on the biogas system [24], [29]. However, in this study, it was seen that the conductivity never exceeded the threshold value making the system efficient and also proving the fact that the OFMSW and SS can be mixed at 5: 1 ratio.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Lee et al [41] reported that methanogenesis occurs efficiently in an anaerobic reactor at pH values between 6.5 and 8.2. Marín-Peña et al [42] also reported that pH values in the range of 7.0-7.5 favor the methanogenic stage of anaerobic digestion. In addition, during the anaerobic co-digestion of 50% orange peel with 50% catering waste, Anjum et al [23] observed that the pH was in the range of 6.38-7.01 between days 39 and 42, which is the optimum range for methanogenesis.…”
Section: Digestion Stage Of the Iscw With CMmentioning
confidence: 96%
“…Most of the EU, except for EU 7, 8, and 9 (inoculum blank), present values below 0.5, indicating the consumption of buffer capacity within the system; the total alkalinity (Table 6) in all the systems presented a low value compared to the recommended levels (13 -15 g CaCO 3 •L -1 ) [ 33]. The electrical conductivity was found to be within normal values for anaerobic processes [34,35]. It is possible to distinguish two groups: those with values below 8 mS •cm -1 (concentration of 7g TVS •L -1 ) and those with values above 8 mS •cm -1 (Concentration of 14 g TVS •L -1 ), indicating that the fed concentration has a direct effect on the electrical conductivity, which may be associated with the salts and seasoning implemented during the cooking processes of the food [36].…”
Section: Bmp Testmentioning
confidence: 99%